How Digital Addiction Fuels Youth Consumerism in India? - Chandra Bhooshan Singh; Dr. Nistha Sharma; Dr. Shinki K Pandey (Involvement International Journal of Business, 2025)
The rise of digital technology has significantly transformed consumer behavior, particularly among young individuals in India. Increased screen time, social media influence, and digital payment methods have contributed to impulsive spending habits. This study examines the impact of digital addiction on youth consumerism, emphasizing psychological, behavioral, and socio-economic factors. This study adopts a qualitative research design with a phenomenological approach with young consumers aged 18–30 in urban India. The data collection focused on digital consumption patterns, purchasing behavior, and financial awareness. Statistical analysis was employed to assess correlations between digital addiction levels and spending habits. Findings indicate that digital addiction significantly influences youth consumerism through instant gratification, Fear of Missing Out (FOMO), and algorithm-driven advertising. Social media platforms and influencer marketing intensify impulsive buying behaviors. The increasing adoption of Buy Now, Pay Later (BNPL) schemes fosters financial instability, pushing many young consumers into debt cycles. Additionally, excessive digital engagement has socio-economic implications, affecting traditional retail businesses and financial well-being. The study highlights the need for regulatory measures, including financial literacy programs and ethical digital marketing practices, to mitigate the negative impacts of digital-driven consumerism. A multi-stakeholder approach involving policymakers, educators, and businesses is essential for promoting responsible digital consumption among Indian youth.